2015
DOI: 10.2320/matertrans.m2014283
|View full text |Cite
|
Sign up to set email alerts
|

Welding of AA 6028 Aluminum Alloy and Its Nanocomposite Using Different Filler Materials

Abstract: The 6000 series aluminum alloys and its composites welded joints suffer from solidification cracking and loss of strength in their fusion zone. Formation of fine equiaxed grains in weld fusion zones is considered one of the best solutions to avoid such problems. AA 6028 aluminum alloy and its nanocomposite (reinforced with 2 mass% Al 2 O 3 ) have been gas-tungsten arc welded with different four filler metals. The first one was Al-12%Si piston alloy. The second, third and fourth ones are Al-6% Si-based reinforc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…For example, Sang-Woo Song et al 1) found that in friction stir welding of dissimilar Al joints the weld formation and mechanical properties of the joints depend on both the material arrangement and conventional welding parameters. Similarly, El-Labban and Mahmoud 2) showed that mechanical properties of welds of Al alloy AA6028 and its nanocomposite (reinforced with 2 mass% Al 2 O 3 ) can be varied by a filler material.…”
Section: Introductionmentioning
confidence: 97%
“…For example, Sang-Woo Song et al 1) found that in friction stir welding of dissimilar Al joints the weld formation and mechanical properties of the joints depend on both the material arrangement and conventional welding parameters. Similarly, El-Labban and Mahmoud 2) showed that mechanical properties of welds of Al alloy AA6028 and its nanocomposite (reinforced with 2 mass% Al 2 O 3 ) can be varied by a filler material.…”
Section: Introductionmentioning
confidence: 97%